Covalent functionalization of germanene employing computational simulations - Denis, Pablo A. (2024)
Computational simulations through density functional theory in conjunction with M06-L and HSE functional have been carried out to investigate the chemical reactivity of the germanene monolayer. It is exceptionally reactive, with an average reaction energy of −60.4 kcal mol−1 for the nineteen functional groups considered: H, F, Cl, Br, O, S, Se, Ge, OH, SH, CH3, CF3, NH, NH2, C6H5, C6H4, CCl2, CBr2, and the azomethine ylide. The results indicate that oxygen is the most reactive reagent (−96.9 kcal mol−1), followed by fluorine (−83.1 kcal mol−1). Germanene presents a rich organic chemistry, and functionalization with azomethine ylides, benzynes, and carbenes can be easily accomplished as indicated by the reaction energies computed, which lie between −45 and −65 kcal mol−1. Furthermore, germanene is significantly more reactive than graphene and hexagonal boron nitride monolayers since the reaction energy for germanene is more than 40 kcal mol−1 lower. Although, in general, germanene is slightly more reactive than black and blue phosphorene and less prone to oxidation, but its oxidation when exposed to air occurs spontaneously. The addition of functional groups works cooperatively. The reaction energies become lower as the number of functional groups increases, thus favouring the agglomeration of functional groups attached unless the steric effect alters this pattern. Finally, we analyzed the electronic properties of functionalized germanene. It is possible to fine-tune the band gap of germanene from 0.1 to 2 eV using different functional groups and coverages. For O-50% and S-50% functionalized germanene, we found that carrier recombination is the most difficult due to the considerable differences between the effective masses of holes and electrons, which is promising for optical applications.